Carbon footprint research and mitigation strategies for rice-cropping systems in China: a review - Ji, Yalan; Zhou, Yongjin; Li, Zhong; Feng, Kaixuan; Sun, Xueyuan; Xu, Youzun; Wu, Wenge; Zou, Huawen (Frontiers in Sustainable Food Systems, 2024)
Reducing greenhouse gas (GHG) emissions and quantifying the carbon footprint (CF) of rice-cropping systems in the context of food security is an important step toward the sustainability of rice production. Exploring the key factors affecting emission reduction in rice production is important to properly evaluate the impact of China's rice-cropping systems on global climate change. This review provides an overview of the direct and indirect CF in rice-cropping systems; analyzes the influencing factors in terms of rice-based cropping systems, varieties and agronomic practices; and proposes mitigation strategies. Different studies have shown that direct and indirect GHG emissions in rice-based cropping systems accounted for 38.3% to 95.5% and 4.5% to 61.7% of total emissions, respectively. And the CFs of ratoon rice, rice-wheat, rice-maize, rice-rapeseed, and rice-fish systems ranged from 316,9 kg CO2-eq kg -1 to 258,47 kg CO2-eq kg -1 , which are lower than that in a double-rice planting system. High-yielding rice, drought-resistant rice, and other hybrids can mitigate GHG emissions from paddy fields by 3.7 21.5%. Furthermore, organic matter, water, tillage, straw incorporation, conservation tillage, reduced nitrogen fertilizer use, and added biochar and methane inhibitors could reduce emissions. Therefore, through reasonable agronomic measures, variety selection and optimal layout of rice-based rotation systems, the carbon neutral rate of rice production can be improved to help the national carbon sequestration and emission reduction target.